Pelatihan Metode Pencatatan Akuntansi Dan Pajak UMKM Dalam Penerapan Program Smart City, Bindu Experience - Wirawan, I Made Dwi Sumba; I Made Dwi Harmana; I Wayan Chandra Adyatma (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2023)
The drastic increase in the number of MSMEs during the pandemic illustrates that small and medium enterprises are one type of industry that is able to survive in crisis conditions. Bindu Village is a village that implements a smart city system with a concept introduced by the village, namely the Bindu Experience. This concept provides an experience of how Bindu Village is a beautiful but dense village with the use of technology, all corners of the village have been reached by WiFi signals. In practice, the use of technology has not been very effective, so the utilisation of these resources can still be improved. The number of people who switch professions to become entrepreneurs makes business activities unable to be carried out professionally, so that business activities are difficult to develop. The main problem is the low awareness of the community in carrying out their obligations as taxpayers, as well as traditional business management without recording every transaction, making it difficult to see whether their business activities are developing or not. The solution offered to overcome these problems is to conduct training, mentoring, and seminars in managing businesses professionally, both in terms of financial management, recording, and business development, it is hoped that this will be able to improve the economy of the community, especially the Bindu Traditional Village. The methods used in community service activities are socialization, focus group discussions, mentoring, training, and entrepreneurial seminars to meet the needs of partners related to improving the economic conditions of their communities affected by the pandemic.